Students' Perception of The Use of English Slang Words In “Diary of a Wimpy Kid” Movie to Improve Vocabulary - Budiarti, Hardiana (English Education Journal, 2024)
Along with the times, language changes and has many varieties. There are many varieties of language development used in everyday life. One of these language varieties is slang. This study focuses on students' perceptions of the use of English slang words in the movie "Diary of a Wimpy Kid" as a tool to improve their vocabulary. This study explores how exposure to colloquial language used in the context of teen movies affects students' vocabulary skills. This study used a qualitative method, employing Partridge's (2016) theory in analyzing the types of slang words in the film and used paired two sample. The participants of this study were 20 students of grade 7 MTs NU 12 Ki Ageng Mataram. This study used the descriptive qualitative research and the questionnaire used in this study is a closed questionnaire type and the researchers used a Likert scale to find out exactly the respondent's answer. The results of this study show that in "Diary of a Wimpy Kid" movie, there are two types of slang: Public school and society slang. The result of students' perception analysis showed that most students (95%) agreed that watching the movie helped them focus in the learning process. The findings suggest that the integration of teaching materials involving popular culture content can be an effective strategy for teaching English vocabulary among teenagers.